2008
DOI: 10.1016/j.neulet.2008.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Temporal profile of potassium channel dysfunction in cerebrovascular smooth muscle after experimental subarachnoid haemorrhage

Abstract: The pathogenesis of cerebral vasospasm after subarachnoid hemorrhage (SAH) involves sustained contraction of arterial smooth muscle cells that is maximal 6 to 8 days after SAH. We reported that function of voltage-gated K + (K V ) channels was significantly decreased during vasospasm 7 days after SAH in dogs. Since arterial constriction is regulated by membrane potential that in turn is determined predominately by K + conductance, the compromised K + channel dysfunction may cause vasospasm. Additional support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…Recently, the function and expression of ion channels, particularly the Ca 2+ -activated K + channels, have been investigated in SAH-induced vasospasm. In the present study, the expression of Ca 2+ -activated K + channels in MCA was largely reduced after SAH in both Ntg and GET-1 mice, which is in agreement with others findings that elevated PKC activity after SAH causes dysfunction in K + channel activity and expression [78,79]. …”
Section: Discussionsupporting
confidence: 93%
“…Recently, the function and expression of ion channels, particularly the Ca 2+ -activated K + channels, have been investigated in SAH-induced vasospasm. In the present study, the expression of Ca 2+ -activated K + channels in MCA was largely reduced after SAH in both Ntg and GET-1 mice, which is in agreement with others findings that elevated PKC activity after SAH causes dysfunction in K + channel activity and expression [78,79]. …”
Section: Discussionsupporting
confidence: 93%
“…Ishiguro et al [116] have found that oxyhemoglobin suppresses voltage-dependent potassium channels in the rabbit cerebral arteries. Of note is that there is little change in the expression of calcium-activated potassium channels after SAH in laboratory dogs, whereas a significant decrease in voltage-gated potassium channels occurs in the arterial smooth muscle cells due to the impact of the oxyhemoglobin [117]. …”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Reduced K V channel function is also observed in dog models of subarachnoid hemorrhage (685) that may be related to decreased expression of K V 2 channel subunits (22, 685). …”
Section: Kv Channelsmentioning
confidence: 98%